2014
DOI: 10.1016/j.celrep.2014.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Inhibition of High-Avidity T Cell Target Lysis by Low-Avidity T Cells via Trogocytosis

Abstract: Summary Current vaccine conditions predominantly elicit low avidity cytotoxic T-lymphocytes (CTLs), which are non-tumor-cytolytic but indistinguishable by tetramer staining or Enzyme-Linked ImmunoSpot from high avidity CTLs. Using CTL clones of high or low avidity for melanoma antigens, we show that low avidity CTLs can inhibit tumor lysis by high avidity CTLs in an antigen-specific manner. This phenomenon operates in vivo: high avidity CTLs control tumor growth in animals, but not in combination with low avid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…Thus, the donor cells seem to retain a sufficient amount of MHCI on their cell surface even after the transfer. However, interestingly, Chung et al recently reported that low-avidity CTLs strip MHCI off target tumor cells via the mechanism of trogocytosis without killing, resulting in an interference with high-avidity CTLs in tumor lysis ( 8 ). It remains unknown whether donor DCs lose the antigen-presenting activity after the release of their MHC molecules to recipient DCs.…”
Section: Antigen Presentation By Mhci-dressed Cells: Cross-dressingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the donor cells seem to retain a sufficient amount of MHCI on their cell surface even after the transfer. However, interestingly, Chung et al recently reported that low-avidity CTLs strip MHCI off target tumor cells via the mechanism of trogocytosis without killing, resulting in an interference with high-avidity CTLs in tumor lysis ( 8 ). It remains unknown whether donor DCs lose the antigen-presenting activity after the release of their MHC molecules to recipient DCs.…”
Section: Antigen Presentation By Mhci-dressed Cells: Cross-dressingmentioning
confidence: 99%
“…In this study, mouse T cells were adoptively transferred to MHC-mismatched mice, and the authors surprisingly found the MHC of the recipient mice on transferred T cells ( 1 ). Since this seminal study, numerous others have shown that the T cell receptor (TCR) rapidly (within minutes) acquires MHC molecules from antigen-presenting cells (APCs) via the immunological synapse formed at cell–cell contact area, and that this phenomenon impacts T cell activation ( 2 8 ), although the physiological relevance of this is still not fully understood. This intercellular transfer of plasma membrane has been called absorption, acquisition, nibbling, shaving, snatching, stripping, or trogocytosis, which is from the ancient Greek Trogo , meaning “gnaw” ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic peptide vaccines can robustly induce a tumor-specific CTL response with limited side effects due to induction of an antigen-specific immune response rather than broad immune activation (18). Preferential development of high avidity anti-tumor CTLs enables enhanced tumor cell killing (8,16). Previously, we showed that vaccine dosages could be optimized to preferentially elicit highavidity CTLs, unlike standard dosages that elicit low-avidity CTLs (14).…”
Section: Discussionmentioning
confidence: 99%
“…We previously developed a mathematical model to study how vaccine-induced avidity selection affects tumor clearance (14). This model was calibrated to ex vivo human data from Chung et al (16) and then validated against data from (17,18). Here, we extend this model to show that induction of immature DCs may improve current treatments by eliciting high-avidity CTLs.…”
Section: Methodsmentioning
confidence: 97%
“…Only recently has the phenomenon of uptake of pMHC molecules from tumor cell membrane by CTLs via trogocytosis been acknowledged [ 36 ]. The emphasis, however, was on the effect of depletion of pMHCs from the tumor surface, snatched by low avidity CTLs, leading to insufficient triggering of high-avidity CTLs and diminished melanoma lysis.…”
Section: Discussionmentioning
confidence: 99%